Integrasi Technological Pedagogical Content Knowledge (TPACK) dengan Information Communation and Technology (ICT) Pada Masa Pandemi Covid 19 di SMA Gema 45 Surabaya - Fifin Dayanti (Intiqad: Jurnal Agama dan Pendidikan Islam, 2021)
Technological developments in the digital world in this millennial era have an impact on the continued development of learning models in educational institutions, one of the learning models that can be an alternative is TPACK integrating learning with digital computer technology so that students are expected to be more innovative and in carrying out the learning process during the covid pandemic. 19. This research method uses qualitative methods with data collection techniques through interviews, observation and documentation. In the 21st century, teachers need to understand and have Technological Pedagogical Content Knowledge (TPACK) competencies. TPACK is a theoretical framework for designing learning models by integrating three main aspects, namely technology, pedagogy, and content. This model has three equally important intersections, namely the intersection between bodies of knowledge expressed as PCK (pedagogical content knowledge), TCK (technological content knowledge), TPK (technological pedagogical knowledge), and TPACK (technology, pedagogy, and content knowledge)